STRATEGI KOMUNIKASI FILANTROPI ORGANISASI DOMPET DHUAFA VOLUNTEER SUMATERA UTARA DALAM FUNDRAISING DI KOTA MEDAN - Ramadhan, Dwiki Zhuri; Harahap, Suheri; Rozi , Fakhrur (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This research is entitled "Philanthropic Communication Strategy of the Dompet Dhuafa Volunteer Organization, North Sumatra in Fundraising in Medan City." The aim of this research is to find out how important and effective the communication strategy carried out by Dompet Dhuafa Volunteer North Sumatra is in Fundraising or collecting funds and communicating with the public. The theory used is the Hierarchy of Effects theory and the Laswell theory model. The research method used in this research is descriptive qualitative methods. By making direct observations at the research location, as well as conducting interviews with relevant informants. After that, carry out documentation in the form of photos. The research results obtained were that the communication strategy carried out was not able to obtain a large response from the audience. Starting from direct and indirect responses.